A problem solving oriented intelligent tutoring system to improve students' acquisition of basic computer skills - Wang, Dongqing; Han, Hou; Zhan, Zehui; Xu, Jun; Liu, Quanbo; Ren, Guangjie (Computers and education, 2015)
Personalization and intelligent tutor are two key factors in the research on learning environment. Intelligent tutoring system (ITS), which can imitate the human teachers' actions to implement one-to-one personalized teaching to some extent, is an effective tool for training the ability of problem solving. This research firstly discusses the concepts and methods of designing problem solving oriented ITS, and then develops the current iTutor based on the extended model of ITS. At last, the research adopts a quasi-experimental design to investigate the effectiveness of iTutor in skills acquisition. The results indicate that students in iTutor group experience better learning effectiveness than those in the control group. iTutor is found to be effective in improving the learning effectiveness of students with low-level prior knowledge. •We model a problem solving oriented ITS architecture.•We develop iTutor to support skills acquisition in real-life problem situation.•A quasi-experimental was designed to investigate the effectiveness of iTutor.•iTutor can better facilitate skills acquisition.•iTutor can improve the skill learning effect of low-level prior knowledge.